'Let's make a good job of it and stay in business': the British distant-water trawler fleet and the coastal mackerel fishery, 1975–1985. (3rd July 2021) - Wilcox, Martin
ABSTRACT: The historiography of British distant-water fishing concentrates on the period prior to 1976 and the third 'Cod War' that saw British trawlers excluded from their principal fishing grounds. Little research has hitherto been done on the period afterwards, during which the industry was obliged to prosecute a variety of fisheries, mostly in home waters, on a seasonal basis. This article partially fills that gap by examining its participation in the coastal mackerel fishery, which during the late 1970s and early 1980s offered the most promising opportunity to keep the fleet employed. However, it forced upon trawler firms a different pattern of operations and required participation for the first time in the burgeoning international market for fish. Despite the difficulties of adapting to this new form of fishing, the mackerel fishery kept the distant-water fleet in business until overfishing, tightening restrictions on catches and the finalisation of the Common Fisheries Policy drove a further wave of contraction in the industry during the early 1980s.